2002
DOI: 10.1079/phn2001282
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and nutritional transition in Mexico: rapid increase of non-communicable chronic diseases and obesity

Abstract: Objective: The objective of this paper is to characterise the epidemiological and nutritional transition and their determinants in Mexico. Design: Age-adjusted standardised mortality rates (SMRs) due to acute myocardial infarction (AMI), diabetes mellitus and hypertension were calculated for 1980-1998. Changes in the prevalences of overweight and obesity in women and children and of dietary intake from 1988 to 1999 were also used in the analysis. Quantities of food groups purchased by adult equivalent (AE) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
249
1
27

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(286 citation statements)
references
References 10 publications
9
249
1
27
Order By: Relevance
“…In Mexico mortality rates due to diabetes, hypertension and acute myocardial infarction have increased dramatically in parallel with the prevalence of obesity in adults and children. Increases in fat intake and purchases of sugar and refined carbohydrates, particularly soda, may be related to increases in overweight, obesity and mortality due to dietrelated causes (Rivera et al, 2002). Figure 1 Weight for age percentiles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Mexico mortality rates due to diabetes, hypertension and acute myocardial infarction have increased dramatically in parallel with the prevalence of obesity in adults and children. Increases in fat intake and purchases of sugar and refined carbohydrates, particularly soda, may be related to increases in overweight, obesity and mortality due to dietrelated causes (Rivera et al, 2002). Figure 1 Weight for age percentiles.…”
Section: Discussionmentioning
confidence: 99%
“…In Mexico, the prevalence of obesity in children under 5 years of age increased from 4.2% in 1988 to 5.3% in 1999 (Rivera et al, 2002). The 2006 National Survey for Health and Nutrition in Mexico found a decrease in stunting of 5-to 11-year-old children from 1999 to 2006 (from 16.1 to 10.4% in boys and from 16 to 9.5% in girls).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, based on the economic difficulties experienced in Mexico during the last ten years, we speculate that recently, diets of a vast section of the population include lower amounts of animal-based foods. Rivera et al 28 found that the purchase of meat and meat-products decreased in the 14 year period from 1984 to 1998. The lack of public health interventions to prevent and treat iron deficiency may contribute to the increase in the prevalence of anemia.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies among US Latinos suggest that dietary acculturation processes may be harmful or protective, depending on dietary patterns, social circumstances and environmental factors in the countries of origin (Kaiser 2009, Perez-Escamilla 2009, Lara et al 2005, Rivera et al 2002, Neuhauser et al 2004, Handley and Grieshop 2007. To explore these processes, investigators have conducted binational studies to help distinguish potentially health-enhancing pre-migration dietary behaviours from those that may be harmful.…”
Section: Introductionmentioning
confidence: 99%